Mean of Modeling of the Informative System of Monitoring of Education is the Class Diagram UML - Ostrey, O.P. (Journal of Information Technologies in Education (ITE), 2008)
In the article the features of functioning of the informational-analytical system for multilevel monitoring of education are considered. The described class diagram UML for the design of the informational-analytical system for multilevel monitoring of higher educational establishment. This diagram describes the static type of the system in relation to processes, represents properties of objects and subjects, their co-operation. Also allows to analyzed the great number of the states of elements of the system.